A latent highly activity energetic fuel: thermal stability and interfacial reaction kinetics of selected fluoropolymer encapsulated sub-micron sized Al particles - Huixin Wang (Nature Portfolio, 2021)
Abstract Aluminum can enhance heat release of energetic composite in theory. However, the commonly used micron aluminum powder has several short comings like incomplete reaction and low reaction rate. Meanwhile, outer oxide shell of nano Al particle is thicker than micro Al, which leads to low active aluminum content and insufficient heat release. On the basis of previous research, reported fluoropolymers modified Al particles were compared and suitable F2311was chosen. Sub-micron scale Al (median particle size around 200 nm) was regarded as optimum coated object in consideration of activity content of aluminum powder changing with particle size. The super fine Al powder was prepared by electrical explosion method, and encapsulated in situ by selected fluorine rubber F2311. The experiments on thermal stability demonstrated F2311 coating thickness should be no less than 3.6 nm. These results were further confirmed by EXPLO5 thermo dynamic calculation. Calculated results showed that reaction characters of F2311 encapsulated Al exceeded conventional nano Al regardless of combustion and explosion. Scanning electron microscopy (SEM), transmission electron microscopy (TEM), laser particle size analyzer and X-ray photoelectron spectroscopy (XPS) were used to characterize coated products’ morphology, particle size distribution and interfacial bonding information. The results showed that the coated samples were generally spherical shape, with median particle size of 217.7 nm and coating thickness of 3.6 nm. The coating shell contained a small amount of alumina and aluminum fluoride besides fluoropolymer. The non-isothermal dynamic equations of Al/F2311 and Al/Al2O3 were deduced by TG/DSC simultaneous thermal analysis. Compared with conventional nano-Al, the apparent activation energy of Al/F2311 decreased by 45 kJ/mol and the first exothermic peak temperature was about 10 °C earlier. Moreover, heat release was nearly twice as conventional nano-Al. TG-DSC-MS coupled measurements certified that active Al was enveloped by ‘fluorine atmosphere’ while F2311 decomposed in range of 200–400 °C. Alumina was replaced with aluminum fluoride inside coating layer during 400–550 °C, which broadened the diffusion path and then accelerated the permeation of oxidizing gas. In addition, the exothermic of Al-F was obviously larger than Al-O. Consequently, the oxidation reaction was activated rapidly, especially in initial exothermic period. Fluoropolymer encapsulated sub-micron sized Al was a latent highly activity energetic fuel and a potential candidate for aluminum powder.